The Effect of Rennin-Angiotensin Blockers on Ejection Fraction in Patients with Left Ventricular Systolic Dysfunction Heart Failure - Mohammed, Salah Mohamed Ibrahim; E.Farah, Mansour; Mekki, Mulhima Mukhtar (Gezira Journal of Health Sciences; Vol 13 No 2 (2017), 2017)
Introduction: Left ventricular systolic dysfunction (LVSD) is a type of heart failure characterized by low ejection fraction (EF) and increase in mortality and morbidity. Rennin- Angiotensin Blockers are confirmed to improve EF and quality of life in patients with LVSD. Objective: The aim of this study was to assess and compare the effect of rennin angiotensin blockers on EF in patient with LVSD. Methodology: 80 patients with LVSD were assigned to use either ACEI (lisinopril) or ARBS (losartan or candesartan); patient’s clinical data and Echocardiography had been followed for 6 months. Results: There was improvement on EF; by 9% in the group taking ACEI (lisinopril) and by 8% in the group taking ARBS. 52.6% of patients showed improvement in their QOL.  Conclusion: There is an improvement on the EF% in the ARBS (losartan or candesartan)  group as well as the ACEI (lisinopril) group. There was no significant difference when comparing the effect of the 2 groups of drugs on the EF%. The quality of life improved in most patients with treatment with these drugs.